Isolamento e caracterização de novos limonoides em Trichilia pallida (Meliaceae) guiado por LC-MS/MS: Uma contribuição à quimiossistemática do gênero - Moraes, Carlos André Ferreira (Universidade Federal de São Carlos, 2025)
The Meliaceae family is widely recognized both for the quality of its wood and for the biosynthesis of tetranortriterpenes (limonoids), secondary metabolites that exhibit various biological activities, including insecticidal, bactericidal, antifungal, and anticancer properties. Several genera within this family have been studied due to the bioactive potential of their compounds, with particular emphasis on Melia L., Toona (Endl.) M. Roem., Azadirachta A. Juss., and Trichilia P. Browne. This last genus has been the subject of phytochemical studies that have demonstrated the presence of the three main classes of limonoids—intact-ring, seco-ring, and rearranged limonoids. However, to date, the occurrence of rearranged limonoids has only been reported in Trichilia species native to Asia. In this study, a methodology was developed based on the monitoring of diagnostic ions detected in fragmentation spectra (MS/MS) to identify potential limonoids and guide the selection of extracts and fractions of Trichilia pallida for the isolation of these metabolites. All extracts and fractions were analyzed using ultra-high-performance liquid chromatography (UHPLC) coupled with a high-resolution mass spectrometer (HRMS). The MS/MS spectra that contained diagnostic ions were used to direct the collection of fractions via high-performance liquid chromatography (HPLC), monitoring absorbance at 215 nm. The methodology employed enabled the isolation and structural characterization, through one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) spectroscopy, of eleven limonoids and two norlimonoids. Among the isolated limonoids, six belong to the C-seco group, one to the A,B-seco group, one has an intact ring, and three underwent structural rearrangement involving the C and D rings. The two norlimonoids (pentanortriterpenes) exhibited the loss of the carbon at position C-12 and modifications in the furan ring, resembling the azadirachtin class. The results obtained in this study suggest that Brazilian Trichilia species exhibit a wide structural diversity of limonoids. The isolation and characterization of previously unreported limonoids for this genus highlight that a more targeted LC-MS/MS approach can reveal the structural richness of these metabolites in Trichilia species native to Brazil.
Isolation and Characterization of New Limonoids from Trichilia pallida (Meliaceae) Guided by LC–MS/MS: A Contribution to the Chemosystematics of the Genus
Keywords: Limonoides; Espectrometria de massas; Elucidação estrutural; Limonoids; Mass Spectrometry; Structural Elucidation; CIENCIAS EXATAS E DA TERRA::QUIMICA; 9. Indústria, Inovação e Infraestrutura